A Person-Centered Approach for Analyzing Multidimensional Integration in Collaboration Between Educational Researchers and Practitioners - Straub, Robin Pascal; Ehmke, Timo (Frontiers in Education, 2021)
Over the past decades, boundary-crossing collaboration among focal stakeholder groups in teacher education (e. g. practitioners, researchers, students) have been increasingly discussed as fruitful pathways for generating integrative didactic innovations. Within this article it will be argued that such collaborative formats resemble socio-organizational innovations in their own right, which in turn provide the necessary prerequisites for advancements in the teaching profession to be co-constructed. Moreover, empirical insights will be provided to further outline boundary-crossing collaboration from a socio-organizational innovation perspective. In order to do so, the conceptual background of this article combines social innovation theory with an analytical framework inspired by the discourse of transdisciplinarity. Social innovation theory highlights for instance the transformation of social relations in order to satisfy social needs and to advocate empowerment, while transdisciplinarity stands for an integrative research and development mode which in addition foster a multi-dimensional understanding of integration (e. g. epistemic, social, organizational). In-depth integration among involved stakeholder groups is again understood as a crucial requirement for successful co-construction and sustainable establishment of socio-organizational innovations. In alignment with that, focal dimensions of integration characteristics (DICs) are operationalized as (1) mutual learning and (2) knowledge integration, (3) perceived-trustworthiness and (4) appreciation within the team and (5) collective ownership of goals. Based on this, an explorative study was conducted in the context of research and development project establishing a collaborative format termed Transdisciplinary Development Teams (TDT). Aim of the study is to further investigate, a) how participating TDT members assess DICs with regards to successful and challenging aspects. In addition, it seeks to b) differentiate types of actors which are characterized by particular assessment patterns. The study employs a complementary mixed-methods design combining qualitative and quantitative approaches and utilizes a data corpus with n = 62 response sets. Subsequently, this article offers a genuine conceptual approach to frame boundary-crossing collaboration in teacher education. In addition, on this basis further empirical insights have been generated which provide some practical implications to support future collaborative endeavor.